Implementation Of Islamic Education Learning (Pai) Design Based Independent Curriculum At Namira Islamic High School Medan - Nazaruddin Nazaruddin; Afrahul Fadhila Daulay; Salamuddin Salamuddin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
One of the presences of the Independent Curriculum is a form of curriculum innovation carried out by the Minister of Education and Culture of the Republic of Indonesia to improve the quality of education. Curriculum innovation refers to using potential part of the curriculum to propose new curriculum ideas or practices in order to solve educational problem or achieve certain goals. This is the case at Namira Islamic High School Medan. Since 2022, it has implemented an independent curriculum based on the demands of being a driving School/pilot School. The research aimed to find out: (1) Independent Curriculum-based PAI Learning Planning at Namira Islamic High School Medan (2) Implementation of Independent Curriculum-based PAI Learning at Namira Islamic High School Medan (3) Evaluation of Independent Curriculum-based PAI Learning at Namira Islamic High School Medan (4) Challenges and Obstacles to Implementing PAI Learning Design at Islamira High School Medan. This research is a type of Qualitative research using observation, interview and documentation methods. Furthermore, the analysis uses a qualitative descriptive method, namely reducing the data that produces findings and then analyzing them to produce conclusive conclusions using an inductive approach. The results of this study generally show that the implementation of Merdeka Curriculum-based PAI learning design at Namira Islamic High School can be carried out well even though it is still in the Learnig by doing adjustment stage. The design begins with consensus (Annual Meeting, Training and Socialization), teaching modules, and determining learning strategies and methods that are PAIKEM GEMBROT (Active Innovative Creative Effective Learning Fun and Totality) and Multimedia. Learning implementation is facilitated by educators as facilitators. Educators are the key to creating independent learning by understanding the totality of the Independent Curriculum learning concept itself. Learning evaluation uses the concept of diagnostic, formative and summative assessments, all of which become a measuring tool for the achievement of student learning outcomes.